A Study on Employees Absenteeism at Private Hospital and Its Research Centre-cross Sectional Descriptive Study - Thakkar, Mital; Wadhwa, Medha; Chatterjee, Subhashish; Gupta, Anubha (International Journal of Psychosocial Rehabilitation, 2020)
According to the International Labor Organization, absenteeism is the practice of an employee who does not show up for work for a period of one or more days when he has been assigned for a day of work. The reasons for the loss of productivity are not always health or disease; some psychological factors, such as personal factors, have effects on absenteeism. Absenteeism among health professionals appears to be a major problem, especially when compared to employees in other sectors. The study is descriptive cross-sectional in nature. The data collection is through a close-ended structured questionnaire in the local language to identify the determinant causes of absenteeism of employees. Employees may take a leave or not report to duty for a variety of reasons, like sickness, emergency, accidents, family commitments such as caring for sick family members, etc. The majority reason behind the absenteeism is family & education reasons.